Supraspinatus tendon transosseous vs anchor repair surgery: a comparative study of mechanical recovery in the rabbit - Chaler, Joaquim; Louati, Hakim; Uhthoff, Hans K; Trudel, Guy (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Supraspinatus (SSP) tendon ruptures requiring surgical repair are common. Arthroscopic suture anchor fixation has gradually replaced transosseous repair in supraspinatus tendon tear. Our objective was to compare mechanical properties between transosseous and anchor supraspinatus repair in the first 6 postoperative weeks in a rabbit model. Methods One hundred and fifty-two rabbits had one supraspinatus tendon repaired either with an anchor suture 1 week after detachment or with transosseous sutures. Rabbits were euthanized at 0, 1, 2, 4 or 6 postoperative weeks. Experimental and contralateral tendons (304 tendons) were mechanically tested to failure. Data are expressed as percent of contralateral. Results Anchor repair had higher loads to failure compared to transosseous repair, at immediate repair (week 0, 52 ± 21% vs 25 ± 17%, respectively; p = 0.004) and at 1 postoperative week (64 ± 32% vs 28 ± 10%; p = 0.003) with no difference after 2 weeks. There was no difference in stiffness. Transosseous repairs showed higher rates of midsubstance failures compared to anchor repairs at 1 (p = 0.004) and 2 postoperative weeks (p < 0.001). Both transosseous and anchor repairs restored supraspinatus mechanical properties after 4 postoperative weeks. Conclusion Anchor repair provided better initial tensile strength while transosseous repair led to a faster normalization (namely, midsubstance) of the mode of failure. Research to optimize supraspinatus repair may need to consider the advantages from both surgical approaches.